Quasi-static and low-velocity impact response on fibre metal laminate - Nur Khaleeda, Romli (2018)
The aim of this research is to investigate the impact behaviour of fibre metal laminates under static and dynamic loading conditions and determine the failure mechanisms of the laminates with different materials such as plain weave carbon fibre reinforced polymer (CFRP), unidirectional prepreg carbon fibre reinforced polymer (CFRP), plain weave glass fibre reinforced polymer (GFRP) and self-reinforced polypropylene polymer (SRPP). The fibre metal laminates (FML) consist of metal and composite fibre. The fibre metal laminates were fabricated by using a compression moulding technique. A type of sheet metal chosen was aluminium alloy 2024-0. The sheet metal was used as top and bottom layer of the fibre metal laminate. A thermoset epoxy was used to laminate the dry fibres (plain weave CFRP and GFRP) with the sheet metal. Then, the laminates would be cured in a room temperature and used a moderate load for pressure application. Meanwhile, the fibre metal laminate, which consisted of prepreg fibre and SRPP was pressed and cured by using a hot press machine. The laminates were pressed then cured at 125°C with pressure of 4 bar. An adhesive film, polypropylene was used and acted as an interlayer in the fibre metal laminates. The polypropylene film was used to bond the SRPP layer to the sheet metal. Variation of materials used, speeds and crosshead speeds are manipulated variables were used to determine the mechanical behaviour of the structures and was investigated. Matrix cracking was found once the structure hit by a maximum load. A continued loading caused plastic deformation in the aluminium system. Fibre breakage and localised delamination in the composite systems as well as debonding at the interface (between aluminium and fibre) and between fibres were observed. The strength of the structure depended on the type of material used and speed. The failure of the structures was due to the initiation of delamination within the composite ply. Quasi-static indentation and low-velocity impact test used Instron 3369 and 9350, which was conducted by different speeds and crosshead speed. The failure mechanism of the fibre metal laminates were found to be similar which under both conditions. The damages were initiated by indentation and impact from a 12.70 mm indenter, which then produced a similar pattern after testing. Finite element models were developed to simulate the mechanical behaviour by using Abaqus finite element package. The finite element results were compared with the experimental results. The failure behaviour of the laminates were predicted and showed a good agreement with the experimental observation. The validation result of finite element analysis in both tests have shown good agreement to experimental measurement. The percentage error for both tests were about 1.43% and 2%. Quasi-static indentation was used to replicate low-velocity impact and was compared between 4.50 m/s and 100 mm/min for Al/CFRP, Al/GFRP, Al/SRPP and Al/CFRP UD. The correlation was evaluated based on energy absorbed to perforate the fibre metal laminate. From the findings, the pattern of during elastic and plastic deformation of quasi-static indentation result was almost identical to low-velocity impact result. When speed increased, maximum force of impact and indentation also increased.